ANALISIS POTENSI ALUMNI PERBANKAN SYARIAH MENJADI SOCIOPRENEURSHIP DI WILAYAH TABAGSEL - Muhammad Isa; Arti Damisa; Ferri Alfadri (Jurnal Akuntansi dan Pajak, 2023)
The purpose to minimize the gap that is created between the fewer Islamic Banking jobs and the increasing number of Islamic banking alumni graduates from time to time with the Sociopreneur analysis of alumni. This research is a Field Research conducted using a descriptive qualitative research approach and using triangulation data analysis techniques. Information about the potential of social entrepreneurship was obtained through literature studies collected from research related to documents, books and journals as assistants and complements to the theories studied. Furthermore, researchers will conduct observations in the form of interviews using the snowball sampling technique directly to alumni of Islamic banking as soicopreneurship actors in the TABAGSEL area and will also conduct interviews with the Head of Islamic Banking Study Program and economists in the TABAGSEL area to strengthen the results of the researcher's findings. The results of the research findings The approach taken by UIN SYAHADA Padangsidimpuan Islamic Banking graduates to change perceptions and inspire the younger generation to become entrepreneurs is to provide knowledge about social entrepreneurship and its benefits and apply a caring attitude towards the surrounding environment and society because this will create a feeling of wanting to help others.